PENDAPATAN USAHATANI JAGUNG VARIETAS HIBRIDA DAN VARIETAS KRISTAL DI DESA PARANG KECAMATAN BANYAKAN KABUPATEN KEDIRI - Nuryati, Ernawati; Widya Fatmawat, Erlin; Nurul Choirina, Vifi (Universitas Islam Balitar, 2025)
Corn is a type of seasonal plant and is a plant that is often cultivated by farmers. Corn has many varieties, one of the varieties of corn planted by farmers in Parang Village is hybrid corn and crystal varieties. The difference in varieties causes fluctuating farmer income. This study aims to determine the difference in income and the difference in costs of hybrid and crystal corn farming in Parang Village, Banyakan District, Kediri Regency. This study took a sample of 60 respondents. The analysis used consisted of income analysis, feasibility analysis, Break Event Point (BEP) analysis, and t-test difference test. The results of the study showed that the income of hybrid corn farming was lower than that of crystal corn farming, which was IDR 8,741,888/ha, while the crystal variety was IDR 11,501,807/ha. The R/C ratio value of hybrid and crystal corn farming is 1.67 and 2.07, so the farming is feasible to be done because it is more than 1. The BEP of hybrid and crystal corn farming units is 2,704 kg/ha and 1,533 kg/ha. The rupiah BEP of hybrid and crystal corn farming is Rp2,868/kg and Rp3,379/kg. The results of the t-test difference test produced a t-count value of 1.848<1.980 and a sig value (2-tailed) of 0.067<0.1, which means that there is a significant difference in costs between hybrid and crystal corn farming.